2019
DOI: 10.1177/2396987318824491
|View full text |Cite
|
Sign up to set email alerts
|

Silent brain infarcts on diffusion-weighted imaging after carotid revascularisation: A surrogate outcome measure for procedural stroke? A systematic review and meta-analysis

Abstract: Aim: To investigate whether lesions on diffusion-weighted imaging (DWIþ) after carotid artery stenting (CAS) or endarterectomy (CEA) might provide a surrogate outcome measure for procedural stroke. Materials and Methods: Systematic MedLine V R database search with selection of all studies published up to the end of 2016 in which DWI scans were obtained before and within seven days after CAS or CEA. The correlation between the underlying log odds of stroke and of DWIþ across all treatment groups (i.e. CAS or CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 198 publications
(198 reference statements)
2
33
0
Order By: Relevance
“…Postoperative DWI abnormalities in the present study were seen in 11.8% (4/34) of the patients, which were roughly in agreement with a meta-analysis study done in CEA patients that demonstrated prevalence of postoperative abnormalities in 10.6% [ 24 ]. Whereas this fact potentially indicates a high clinical demand for intraoperative evaluation of DWI abnormalities, the conventional SEPs in the present study indicated low sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Postoperative DWI abnormalities in the present study were seen in 11.8% (4/34) of the patients, which were roughly in agreement with a meta-analysis study done in CEA patients that demonstrated prevalence of postoperative abnormalities in 10.6% [ 24 ]. Whereas this fact potentially indicates a high clinical demand for intraoperative evaluation of DWI abnormalities, the conventional SEPs in the present study indicated low sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the MRI which performed on the post-operation patients contemporaneously revealed the emerging hyperintense signals in DWI sequences. So the DWI (+) shown in the operative patients maybe ascribe to the particulate embolism after CAS [11] . Because astrocytes are very sensitive to cerebral ischemia and hypoxia, the embolism could cause the astrocytes damaged and produced excessive GFAP and S100B into CSF.…”
Section: Discussionmentioning
confidence: 97%
“…Some researchers pointed out that the ischemic brain lesion after CAS could increase the risk of recurrent cerebrovascular events [10] . So they recommended the application of Diffusion Weighted Imaging (DWI) as a surrogate outcome measure for procedural stroke in carotid revascularisation procedure [11] . But the two above imaging tools in some extent have the disadvantages of poor repeatability, high costs and susceptible to the operators.…”
Section: Introductionmentioning
confidence: 99%
“…2 DWI lesions qualify as a strong surrogate measure as they meet three conditions: (i) a plausible biological relationship with stroke; 3 (ii) an association with increased risk of post-procedural stroke/transient ischaemic attack); 4 and (iii) the treatment effect on DWI lesions correlates with that on stroke. 5 According to these three qualifications, DWI lesions quantified as number and/ or volume are an excellent surrogate endpoint for studies evaluating treatment modifications.…”
mentioning
confidence: 99%
“…A 2019 meta-analysis established that for an underlying 3% absolute difference in procedural stroke risk among revascularisation techniques, a 90% sample size reduction could be achieved when using DWI lesions rather than classic endpoints. 5 Of note, little is known about the optimal timing of the post-procedural scan as both ongoing haemodynamic disturbance and thrombo-embolic events days after the procedure are common. Also, magnetic resonance (MR) field strength may influence the number of DWI lesions, 2 and thus timing and image acquisition protocols should be harmonised in future research.…”
mentioning
confidence: 99%